Evidence for the transmission of parvovirus B19 in patients with bleeding disorders treated with plasma‐derived factor concentrates in the era of nucleic acid test screening. Issue 6 (24th September 2012) - Soucie, J. Michael; De Staercke, Christine; Monahan, Paul E.; Recht, Michael; Chitlur, Meera B.; Gruppo, Ralph; Hooper, W. Craig; Kessler, Craig; Kulkarni, Roshni; Manco‐Johnson, Marilyn J.; Powell, Jerry; Pyle, Meredith; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND: Parvovirus B19 (B19V) is a small, nonenveloped virus that typically causes a benign flu‐like illness that occurs most frequently in childhood. The virus is resistant to current viral inactivation steps used in the manufacture of antihemophilic factor concentrates and B19V transmission through these products has been documented. Since 2000, B19V nucleic acid test (NAT) screening of plasma pools has been implemented to further decrease the viral burden in these products, but no study has examined populations using these products to assess the impact of the screening on B19V transmission. STUDY DESIGN AND METHODS: Blood specimens obtained from participants of a surveillance system established in federally supported specialized bleeding disorders clinics were used in a B19V seroprevalence study. RESULTS: A total of 1643 specimens from 1043 participants age 2 to 7 years born after B19V NAT screening was implemented were tested. Age‐specific prevalence rates were generally higher for subjects exposed to either plasma‐derived products alone or in combination with other products compared to subjects with no exposure to antihemophilic products. Overall, compared to participants unexposed to blood or blood products, those exposed to plasma‐derived products alone were 1.7 times more likely to have antibodies to B19V (p = 0.002). CONCLUSION: These results are consistent with continued B19V transmission through plasma‐derived factor concentrates. Effective viral inactivation and detection processes are needed to protect users of these products from infection with B19V or other new or emerging viruses.